Intra-oral orthosis vs amitriptyline in chronic tension-type headache: a clinical and laser evoked potentials study - de Tommaso, Marina (BioMed Central, 2006)
BACKGROUND: In the present study, we examined clinical and laser-evoked potentials (LEP) features in two groups of chronic tension-type headache (CTTH) patients treated with two different approaches: intra-oral appliance of prosthesis, aiming to reduce muscular tenderness, and 10 mg daily amitriptyline. METHODS: Eighteen patients with diagnosed CTTH participated in this open label, controlled study. A baseline evaluation was performed for clinical features, Total Tenderness Score (TTS) and a topographic analysis of LEPs obtained manually and the pericranial points stimulation in all patients vs. healthy subjects. Thereafter, patients were randomly assigned to a two-month treatment by either amitriptyline or intra-oral appliance. RESULTS AND DISCUSSION: Both the intra-oral appliance and amitriptyline significantly reduced headache frequency. The TTS was significantly reduced in the group treated with the appliance. The amplitude of P2 response elicited by stimulation of pericranial zones showed a reduction after amitriptyline treatment. Both therapies were effective in reducing headache severity, the appliance with a prevalent action on the pericranial muscular tenderness, amitriptyline reducing the activity of the central cortical structures subtending pain elaboration CONCLUSION: The results of this study may suggest that in CTTH both the interventions at the peripheral and central levels improve the outcome of headache.